Tricky choices between short or long-term financial sustainability: cost allocation for medical malpractice claims in Italy - Milena Vainieri; Andrea Vandelli; Davide Trinchese (Cogent Business & Management, 2024)
Financial sustainability is a recurring challenge for public organizations and is closely linked to resource allocation. Medical malpractice claims can significantly impact public healthcare costs, prompting several countries, including Italy, to adopt different strategies for managing these risks. These strategies range from insurance-based systems to self-insurance models. While the former offers greater long-term security, it tends to be more expensive in the short term. Conversely, self-insurance, if properly implemented, can provide both adequate protection and cost savings. However, it also carries the risk of incentivizing opportunistic behavior aimed at achieving short-term financial gains. This study explores the propensity of Italian healthcare organizations to choose between these approaches and the relationship between their choice and short-term financial viability. A quantitative analysis of the relationship between premiums, provisions, and financial indicators, such as ROA and ROS provides empirical evidence of potential opportunistic behavior. Additionally, semi-structured interviews are conducted to validate the interpretations from the statistical analyses. Our findings reveal that many regional administrations have insufficient coverage for risk exposure, which may temporarily improve financial performance but increase the risk of long-term financial instability.
Keywords: 650; Public organizations; cost allocation; financial sustainability; medical malpractice; healthcare management